The Impact of Building Regulation Contravention on Rapid Urbanisation: Case of Kano Metropolis - fnia, Sani Khalil Ibrahim (European Journal of Sustainable Development, 2019)
An increasingly urbanizing world has made building regulation central to the organized development of cities world-wide. It is noted that half of the world’s population is now living in cities. The world urban population is expected to increase by 84% by 2050, from 3.4 billion in 2009 to 6.3 billion and will happen in developing countries. Also projected in the next 20 years, over 95% of this population growth will occur in urban areas. Kano is among the fast urbanizing cities in the West African sub region. This paper focuses on the implication of building regulation contravention in Kano metropolis and its impact on the sustainability in mixed land-use areas. It identifies and documents the key drivers of contravention. The findings are expected to create the platform for developing a conceptual framework that might improve compliance to sustainable development regulation regime in Kano metropolis. The significance of the findings is expected to form the foundation towards development compliance procedures for a more sustainable urbanization process in the sub-region. Like Kano, Cities play vital role globally and nationally, as economic, social, cultural and political centers. To successfully achieve this, urbanization should sustainably be driven. Data was collected through Visual survey, interview and questionnaires and subjected to descriptive analysis. Preliminary findings indicate negative perception of current building approval and enforcement procedures in Kano. Keywords: Building Regulations, Contraventions, Sustainable Development, Compliance Procedures and Enforcement